Maternal and Fetal Implications of Gestational Diabetes Mellitus: A Retrospective, Longitudinal Study - Sanjay A. Gupte; Chandrakant Rao; Gayatri Venkataraman; Aarti S. Shah; Shweta M. Jangam; Manasi Kunte; Deepti Salunkhe; Shridevi Gundu (Clinical Diabetology)
OBJECTIVE: This study followed Diabetes in Pregnancy Study Group India (DIPSI) guidelines and compared the clinical profiles, and maternal and fetal outcomes of pregnant women with gestational glucose intolerance (GGI) and gestational diabetes mellitus (GDM). MATERIAL AND METHODS: This retrospective, single-center study analyzed data from 958 pregnant women between April 2019 and March 2022. All women underwent an oral glucose tolerance test (OGTT) and, based on OGTT values, were categorized as normal, GGI, GDM, or diabetes mellitus (DM). RESULTS: The mean ages for GGI, GDM, and DM groups were 31.14, 31.39, and 33.00 years, respectively. Significant differences were observed in body mass index (BMI), which was highest in the DM group (p = 0.001). Increased conversion rates to GDM were noted in the third trimester. Conversion from GGI to GDM (p = 0.1142) was lower than from normal to GGI (p = 0.005) or GDM (p = 0.006). Women with a family history of diabetes, particularly with both parents affected, had a higher risk of GDM/DM. GDM and DM were associated with adverse outcomes like history of abortion, stillbirth, intrauterine growth restriction, low birth weight, and large-for-gestational-age infants. Preterm birth and oligohydramnios were highest in the DM group. CONCLUSIONS: GGI and GDM are associated with maternal and fetal health, increasing the risk of complications. Identification, and appropriate monitoring and management of GGI may help reduce the conversion into GDM and help prevent future adverse outcomes.